Characteristics of the treatment by prisoners of war and captured members of federal forces during the 1991 independence war in Pomurje - ŠTEINER, ALOJZ (Anali PAZU HD, 2023)
Independence War 1991 in Pomurje is presented in numerous publications. They also contain information of the treatment by prisoners of war and captured members of federal forces and prisoners' assembly points. The paper is based on the survey and analyses of a subject, considering some of the non-clearing matters. At the same time, through an objective presentation, the character of the Slovenian independence war is shown.The paper describes the recall and appeal for the accession of JLA members to the Slovenian Defence Force and terminological embarrassments in relation to international law of war and practice in Slovenia in 1991. The functional demarcation and responsibilities for prisoners' assembly points between territorial defence and the Internal Affairs Authorities is explained. Also, the formation and operation of prisoners' assembly points and centers, with certain specificities in Pomurje, are described. To this is added a comparison of the number of deserted and captured in conflicts in Slovenia and Pomurju 1991 with the indicators of the numerical status. The findings of the survey are followed by conclusions and conclusions. Some of these are as they have not been presented before.
Keywords: Independence War 1991 in Pomurje; prisoner of war; captured member; prisoners' assembly point; international law of war